2013
DOI: 10.2106/jbjs.l.00307
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction and Plate Fixation Versus Nonoperative Treatment for Displaced Midshaft Clavicular Fractures

Abstract: Open reduction and plate fixation reduces the rate of nonunion after acute displaced midshaft clavicular fracture compared with nonoperative treatment and is associated with better functional outcomes. However, the improved outcomes appear to result from the prevention of nonunion by open reduction and plate fixation. Open reduction and plate fixation is more expensive and is associated with implant-related complications that are not seen in association with nonoperative treatment. The results of the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
303
4
16

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(336 citation statements)
references
References 18 publications
13
303
4
16
Order By: Relevance
“…Fourth, the QuickDASH score is not specifically designed for patients with a displaced midshaft clavicle fracture. Nevertheless, it often is used as one of the tools to measure function [1,4,[18][19][20]. Fifth, because patients experience and recall symptoms differently, we know this study could be susceptible to recall bias.…”
Section: Discussionmentioning
confidence: 98%
“…Fourth, the QuickDASH score is not specifically designed for patients with a displaced midshaft clavicle fracture. Nevertheless, it often is used as one of the tools to measure function [1,4,[18][19][20]. Fifth, because patients experience and recall symptoms differently, we know this study could be susceptible to recall bias.…”
Section: Discussionmentioning
confidence: 98%
“…Collation of literature on clavicle fractures suggests that the expected nonunion rate is 8.6%. This percentage was derived from the reported healing rate in 12 separate publications [59][60][61][62][63][64][65][66][67][68][69][70] spanning the period from 2004 to 2013 and including 3168 patients treated with a range of conservative and operative methods. Both samples are large, and the nonunion rate in our database again differs by less than a percentage point from the literature values.…”
Section: Discussionmentioning
confidence: 99%
“…2,[5][6][7][8] However, more recent studies have suggested that operative treatment results in increased patient satisfaction, superior functional capabilities, and decreased rates of nonunion and malunion when compared with nonoperative management. [9][10][11][12] Operative management of midshaft clavicle fractures may involve the use of various techniques for reduction and fixation. 12 Currently, open reductioneinternal fixation is considered the gold-standard treatment because of the immediate rigid stability provided by the fixation device.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In addition, autologous iliac crest bone graft (ICBG) has proved to augment osteosynthesis during fixation of nonunion fractures through the release of osteogenic factors. 2,11,[13][14][15][16][17] However, studies have associated ICBG harvesting with significant donor-site morbidity, including neurologic and vascular injury, incisional hernia, donor-site fracture, and deep infection. [21][22][23][24] Therefore, the purpose of this article was to describe a surgical technique developed to reduce donor-site morbidity and improve functional outcomes after open reductioneinternal fixation with autologous bone graft placement through local autograft harvesting and concurrent plate fixation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation